2020
DOI: 10.1038/s41598-020-58998-1
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Thermoelectric Properties of Mg2Sn Single Crystals via Point-Defect Engineering

Abstract: is a potential thermoelectric (te) material that can directly convert waste heat into electricity. in this study, Mg 2 Sn single-crystal ingots are prepared by melting under an Ar atmosphere. the prepared ingots contain Mg vacancies (V Mg) as point defects, which results in the formation of two regions: an Mg 2 Sn single-crystal region without V Mg (denoted as the single-crystal region) and a region containing V Mg (denoted as the V Mg region). the V Mg region is embedded in the matrix of the single-crystal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(102 citation statements)
references
References 46 publications
12
90
0
Order By: Relevance
“…In light of the ubiquitous nature of intertemporal decisions, there has been much interest in identifying their cognitive and neural mechanisms. Animal models generally agree with brain imaging studies on the recruitment of a valuation network involving the ventral striatum and ventromedial prefrontal cortex [9][10][11][12][13][14][15][16]. Striking discrepancies, however, are reported across animal and human studies with regard to the recruitment of the medial temporal lobe.…”
Section: Introductionsupporting
confidence: 58%
“…In light of the ubiquitous nature of intertemporal decisions, there has been much interest in identifying their cognitive and neural mechanisms. Animal models generally agree with brain imaging studies on the recruitment of a valuation network involving the ventral striatum and ventromedial prefrontal cortex [9][10][11][12][13][14][15][16]. Striking discrepancies, however, are reported across animal and human studies with regard to the recruitment of the medial temporal lobe.…”
Section: Introductionsupporting
confidence: 58%
“…First, compared to the thermal conductivities of pure Mg 2 Si (7.9 W m –1 K –1 ) and Mg 2 Sn (5.9 W m –1 K –1 ), the thermal conductivities of Mg 2 (Si, Sn) solid solutions are significantly reduced. It is reported that Mg interstitials and/or (Si, Sn) vacancies should exist as possible intrinsic point defects in the Mg 2 Si phase and the Mg 2 Sn phase, regardless of used fabrication processes and chemical compositions. Thus, these point defects would also exist with a certain probability in the Mg 2 (Si, Sn) solid solutions, and it is certain that random occupations of Si and Sn in the same site of Mg 2 (Si, Sn) are the dominant point defects (solute Sn atoms in Mg 2 Si and solute Si atoms in Mg 2 Sn) to strengthen phonon scattering due to large elastic strain around random solute atoms. Furthermore, both alloys containing the gradient composition layered microstructure exhibit relatively lower κ as compared to other Mg 2 (Si, Sn) alloys with no gradient composition layered microstructure, such as that of Mg 2 Si 0.25 Sn 0.75 in ref .…”
Section: Resultsmentioning
confidence: 96%
“…After centrifugation at 100,000× g , for 2 h 15 min at 4 °C (MLA-55 in Optima MAX-XP, Beckman Coulter), supernatant was aspirated, the pellet suspended in 60 μL of PBS and aliquots stored at −20 °C until analysis. The described procedure enables isolation of sEVs and exclusion of most lipoproteins from plasma, as determined for 10 healthy volunteers by electron microscopy, nanoparticle-tracking analysis, asymmetrical flow field-flow fractionation connected to detectors and miRNA expression analysis [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%